PEMETAAN ZONA AGROKLIMAT SCHMIDT FERGUSON MENGGUNAKAN DATA STASIUN PENGAMAT HUJAN DAN PRODUK DATA SATELIT IMERG DI PROVINSI BALI - Putranto, Wahyu Widodo; Nuarsa, I Wayan; Kartini, Ni Luh; Andi Yuda, I Wayan; Wiratmaja, I Made Dwi (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2022)
Schmidt Ferguson map based on rainfall data is utilized to maximize agricultural potential by knowing the spatial pattern of agro-climatic zones. This study aims to produce Schmidt Ferguson agro-climatic zone by corrected IMERG Satellite rainfall data by station base data in Bali Province. The length of monthly rainfall data from each source is six years (2015 – 2016). Initially, IMERG Final Precipitation data level 3 is validated to 73 rainfall observation stations over Bali. Statistical methods used for this purpose are correlation coefficient (r), Root Mean Square Error (RMSE) and paired t-test. The validation results show a good correlation value of 0.62 – 0.93, RMSE value of 63.33 – 208.86 mm, the results of the paired t-test there are significant. Hereinafter, IMERG data are corrected by simple linear regression equation y = 0.905x + 4.0979 with an R2 value of 0.5878. The Schmidt Ferguson agro-climatic zone mapping from rain observation station data resulted in 5 climate zones, namely climate zone B, C, D, E, and F and from IMERG product data, 4 climate zones, namely climate zone B, C, D, and E. Keywords: Observation; IMERG;Data Validation; Schmidt Ferguson Agroclimate Zone